EZID: A new approach to hazard identification during the design process by analysing energy transfers. (June 2017) - de Galvez, Nicholas; Marsot, Jacques; Martin, Patrick; Siadat, Ali; Etienne, Alain
Graphical abstract: Highlights: In France, in 2014, machines were involved in more than 30 000 working accidents. Machine designers do not have proper means to realize a clean integrated prevention. Works about integrated prevention are focused on risk assessment and risk reduction. EZID uses the fact that hazards are linked to energy to identify hazards properties. Abstract: Manufacturing machine designers must take into account different aspects of products such as technology, legislation and occupational safety. European directive 2006/42/CE promulgates machine safety design principles to prevent occupational risks. Aimed at machine designers, its objective is to set out the need to obtain the lowest possible risk level according to the state of the art. Although the designers of catalog machines have access to specific standards to perform a priori risk analyses, this is not the case for special machine designers. An original approach called EZID is presented in this paper to help all machine designers in the task of hazard identification. Based on the fact that hazards are linked to the presence of energies, EZID identifies hazards through the detection of design parameters linked to energy sources and flows. It then feeds back organized information to designers on every potential exchange of energy between the machine and its operators, bringing to light the need to add risk prevention solutions. The first part provides a detailed classification of energy parameters considered to be the primary indicators of hazards. This is followed by an explanation of the logical rules describing how damage is generated by the combination of the other design parameters, increasing the level of detail in hazard identification. The next part focuses on the characterization of significant hazards. Finally, the results obtained from using this approach during the industrial design of a supply line are presented to confirm that EZID is functional from the earliest stage of design.